Challenges in Federal Facility Control System Cyber Security, Including Level 0 and 1 Devices - Joseph Weiss (The National Academies Press, 2023)
Cybersecurity for Level 0 and Level 1 devices - which include sensors, the Industrial Internet of Things, and operate on a time scales ranging from milliseconds to seconds - is underdeveloped. This Federal Facilities Council white paper addresses changes to improve cybersecurity, productivity, process safety, predictive maintenance, and resilience, while also breaking down cultural and organizational barriers. This is not a publication of the National Academies of Sciences, Engineering, and Medicine. The views expressed in this publication are solely those of the author and do not necessarily reflect the views of the National Academies of Sciences, Engineering, and Medicine.
Keywords: Computers and Information Technology

Collective and Individual Actions to Envision and Realize the Next Era of America’s Transportation Infrastructure: Phase 1 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The American Association of State Highway and Transportation Officials (AASHTO) and TRB's National Cooperative Highway Research Program (NCHRP) have initiated a multi-year process to describe and advance the implementation of a vision for the next era of transportation in the United States.NCHRP Research Results Digest 404: Collective and Individual Actions to Envision and Realize the Next Era of America’s Transportation Infrastructure: Phase 1, from NCHRP, explores and articulates what state DOTs can do collectively and individually to establish and realize a transformative vision of the next era of America’s transportation infrastructure, a vision and infrastructure to support the nation’s continued prosperity and well-being.Supplemental to the digest is a document containing Appendices A through K.
Keywords: Transportation and Infrastructure

Becoming a Tech-Savvy DOT of Tomorrow (The National Academies Press, 2023)
Over the last several years, the transportation industry has been presented with multiple technologies and trends that have "disrupted" business as usual at state departments of transportation (DOTs) and other transportation agencies. These technologies include everything from new transportation modes (such as scooters) to new data sources, communication technologies, and trends (such as the growth in e-commerce); they present challenges as well as opportunities for transportation agencies in both performance and customer service. NCHRP Research Report 1075: Becoming a Tech-Savvy DOT of Tomorrow, from TRB's National Cooperative Highway Research Program, provides a playbook for agencies to follow for defining and strategically addressing the impacts of disruptive technologies on transportation outcomes and on the performance of business units within DOTs. Supplemental to the report are NCHRP Web-Only Document 371: Impact of New Disruptive Technologies on the Performance of DOTs and a Disruptive Tech Handout.
Keywords: Transportation and Infrastructure

Airport Insurance Requirements - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
An airport’s insurance program is just one component of its overall risk management program. An insurance program can be quite complex, addressing types of coverage, limits, retention amounts, and legal and contractual issues, among other factors. The TRB Airport Cooperative Research Program's ACRP Research Report 248: Airport Insurance Requirements provides best practices for airports developing an insurance program, including requirements for contracts with third parties doing business at the airport. Supplemental to the report are a Brochure and Insurance Coverage Templates.
Keywords: Transportation and Infrastructure

State Transportation Agency Decision-Making for System Performance: Conduct of Research Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Transportation agencies must grapple with a broad range of trends and issues that influence and act upon the systems they manage and operate. Issues include climate change, goods movement, changing centers of population and economic activity, and telework, among others.NCHRP Web-Only Document 345: State Transportation Agency Decision-Making for System Performance: Conduct of Research Report, from TRB's National Cooperative Highway Research Program, depicts the relationships among trends, issues, and system objectives.The report is supplemental to NCHRP Research Report 1042: State Transportation Agency Decision-Making for System Performance: Practitioner’s Playbook.
Keywords: Transportation and Infrastructure

Guide to Recruiting, Developing, and Retaining Transportation Infrastructure Construction Inspectors - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Transportation construction inspectors (CIs) have specific expertise in areas such as earthwork, structures, and pavement. CIs apply this expertise to ensure that construction work meets or exceeds the construction contract requirements. State departments of transportation are facing attrition in the CI workforce and losses in institutional knowledge among CIs as a result of retirements, agency downsizing, and fewer individuals pursuing construction inspection. The number of candidate CIs is projected to be inadequate to meet current and future needs.The TRB National Cooperative Highway Research Program's NCHRP Research Report 1027: Guide to Recruiting, Developing, and Retaining Transportation Infrastructure Construction Inspectors describes approaches that state DOTs can use to build and sustain a construction inspection workforce.Supplemental to the report are NCHRP Web-Only Document 337: Training and Certification of Construction Inspectors for Transportation Infrastructure, an Implementation Memorandum, and a Dissemination Presentation.
Keywords: Transportation and Infrastructure

Memorial Tributes: Volume 25 - National Academy of Engineering (The National Academies Press, 2023)
This is the twenty-fifth volume in the Memorial Tributes series compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and international members. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who have personal knowledge of the interests and engineering accomplishments of the deceased.
Keywords: Biography and Autobiography

Risk-Based Construction Inspection: Conduct of Research Report (The National Academies Press, 2023)
Limited availability of construction-inspector resources for transportation infrastructure is a major challenge and can lead to accepting material or workmanship without sufficient examination, which can result in quality risks, safety concerns, functional failures, and reduced performance life of highway infrastructure. NCHRP Web-Only Document 344: Risk-Based Construction Inspection: Conduct of Research Report, from TRB's National Cooperative Highway Research Program, is supplemental to NCHRP Research Report 1039: Risk-Based Construction Inspection: A Guide.
Keywords: Transportation and Infrastructure

E-Scooter Safety: Issues and Solutions - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Electric scooter (or e-scooter) usage continues to expand worldwide with shared, rented, and privately owned devices. While many communities with e-scooter sharing programs have observed social, health, economic, and environmental benefits of enhanced multimodal travel and having more alternatives to vehicle use, these effects are often accompanied by real and perceived safety challenges.BTSCRP Web-Only Document 5: E-Scooter Safety: Issues and Solutions, from TRB's Behavioral Traffic Safety Cooperative Research Program, seeks to build upon existing research to date, identify key gaps in knowledge and data related to e-scooter behavioral safety, and develop evidence-based guidance that can enhance the coordination of behavioral safety programs and countermeasures with a broader toolbox of approaches to improve safety for all road users.The document is supplemental to BTSCRP Research Report 9: E-Scooter Safety Toolbox.
Keywords: Transportation and Infrastructure

Framework for Implementing Constructability Throughout Project Development from NEPA to Final Design (The National Academies Press, 2023)
Since the inception of using sets of plans for construction purposes, a persistent challenge has been the miscommunication between designers and constructors, even when they were part of the same organization. NCHRP Web-Only Document 388: Framework for Implementing Constructability Throughout Project Development from NEPA to Final Design, from TRB's National Cooperative Highway Research Program, develops a decision-making framework that is scalable to all contract delivery methods and that complies with all environmental statutory requirements. Supplemental to the report are a technical memorandum, an adaptation guide for the framework toolkit, a full presentation, and an abridged presentation.
Keywords: Transportation and Infrastructure

Transformation in Wireless Connectivity: Guide to Prepare Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The main wireless applications at airports—passenger connectivity and airport staff communications—are imposing increasing demands on wireless capacity. Demand for passenger mobile connectivity is skyrocketing as high-speed-capable devices proliferate, and passengers require enhanced connectivity either for work or entertainment during dwell times, including location-based services for a custom travel experience. The TRB Airport Cooperative Research Program's ACRP Research Report 242: Transformation in Wireless Connectivity: Guide to Prepare Airports is intended as a resource for airports as they navigate through the existing taxonomy of wireless technologies and their use cases. ACRP WebResource 15: Assessment Tool for Transformation in Wireless Connectivity is an assessment tool that supports the methodology outlined in the report. It provides a dynamic interface to input the current status of the wireless technology implementation at an airport and to input the intended goals regarding the development of the airport’s wireless infrastructure/use cases and generates a report that comprehensively compares the indicated current and target statuses. Supplemental to the report is a PowerPoint presentation that can be used by airport decisionmakers on proposed solutions.
Keywords: Transportation and Infrastructure

The Coast Guard’s Next Decade: An Assessment of Emerging Challenges and Statutory Needs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
In the face of climate change, technological innovation, and global strategic competition, the U.S. Coast Guard will need to respond to many developments in the maritime domain over the next decade. The Coast Guard likely has sufficient statutory authority to respond to most of these developments, but some developments may call for new or clarified statutory authority as well as coordination with international bodies. Current statutory manning requirements, for example, will limit the Coast Guard’s ability to authorize the regulated use of uncrewed vessels with autonomous systems. New authority may also be needed to establish spaceflight-related safety zones applicable to foreign-flagged vessels within 200 nautical miles of the U.S. coastlines.These are among the findings in TRB Special Report 346: The Coast Guard’s Next Decade: An Assessment of Emerging Challenges and Statutory Needs from the Transportation Research Board of the National Academy of Sciences, Engineering, and Medicine.The report emphasizes that in addition statutory authority, the Coast Guard will need key organizational and operational capabilities, including a well-trained workforce, to respond to future challenges. A short video charts the Coast Guard's next decade.
Keywords: Transportation and Infrastructure

Impact of New Disruptive Technologies on the Performance of DOTs (The National Academies Press, 2023)
Technology is at the core of the surface transportation system and is embodied in existing and new scientific knowledge and infrastructure, hardware, and software processes. It is designed to improve performance and cost-effectiveness of infrastructure and the vehicles, systems, and services that utilize the infrastructure. In recent years, a series of rapid advances in key technology areas such as sensors, communications, artificial intelligence, energy storage, nanomaterials, and robotics have combined to provide the potential to improve the performance and safety of the transportation system as well as the agencies’ organizational capabilities to manage performance. Firms are remixing decades-old “core” technologies of the Internet, mobile and cloud computing, artificial intelligence and machine learning (AI/ML), robotics, and additive manufacturing (3D printing) with new business models to create new forms of work and mobility. NCHRP Web-Only Document 371: Impact of New Disruptive Technologies on the Performance of DOTs, from TRB's National Cooperative Highway Research Program, is supplemental to NCHRP Research Report 1075: Becoming a Tech-Savvy DOT of Tomorrow and develops a guide for state DOTs and other transportation planning agencies to understand, predict, plan for, and adapt to the potential impacts of emerging disruptive technologies.
Keywords: Transportation and Infrastructure

2023 Nobel Prize Summit: Truth, Trust, and Hope: Proceedings of a Summit - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On May 24-26, 2023, the Nobel Prize Summit entitled Truth, Trust, and Hope was convened as a hybrid event to examine misinformation and disinformation in the context of the broader information ecosystem, looking at the global impact of information technologies in nature and society. The summit brought together Nobel laureates, leading scientists, business leaders, writers, artists, and young innovators to share insights, challenges, and solutions relating to trust and information. With a positive narrative and the accelerating prevalence of artificial intelligence, big data, and other emerging information technologies, the summit explored the challenges and opportunities of democratization of knowledge and information and the erosion of trust. Held in Washington, DC and virtually, the 3-day summit attracted more than 700 in-person attendees and more than 10,000 online participants from more than 70 countries. Eleven Nobel laureates were actively engaged in the summit, and 32 partner organizations were involved, including breakout sessions and solution sessions. This publication summarizes the presentations, activities, and discussion of the summit.
Keywords: Policy for Science and Technology